Correlation between Acute Phase Symptoms with Neurological Long Covid Symptoms on COVID-19 Survivors - Ganiem, Ahmad Rizal; Siuliyanty, Siuliyanty; Ong, Anam; Gamayani, Uni; Amalia, Lisda; Wibisono, Yusuf (Faculty of Medicine Universitas Padjadjaran, 2023)
Objective: To investigate prolonged neurological impacts of COVID-19 and establish a connection between initial COVID-19 symptom severity and chronic fatigue syndrome (CFS) development, poor sleep quality (PSQ), and cognitive impairment (CI) in individuals recovered from COVID-19.Methods: This cross-sectional study recruited COVID-19 survivors at Dr. Hasan Sadikin General Hospital Bandung, Indonesia, between June and December 2021. All participants gave informed consent and underwent interviews on demography, clinical features, long-COVID questionnaire, and neurological examination. Participants underwent cognitive examination (MOCA-INA), Chalder Fatigue Scale and Pittsburgh Sleep Quality Index (PSQI) to assess CI, CFS, and PSQ variables. Chi-Square analysis was performed to determine the probability of neurological long COVID-19 syndrome manifestations using SPSS 24.0.Results: Of the 127 participants recruited, 67.7% were women, median (IQR) age of 33 (21-65) years, and time from hospitalization to examination of nine months (1-13). The most common neurological Long COVID symptoms were PSQ (59.8. %), CFS (51.2%), and CI (33.9%). Participants with more than five acute phase COVID-19 symptoms had a higher probability of CFS and CI (OR 2.38 (1, 16-4.9, CI 95%); OR 2.20 (1.01-4.79, CI 95%)) than those with less than five symptoms. The study did not find a significant correlation between sleep quality and number of acute-phase COVID-19 symptoms (OR 1.56 (0.76-3.20, CI 95%)).Conclusion: Almost two-thirds of the COVID-19 survivors experienced PSQ, more than half had CFS, and almost one-third had CI. The study revealed an increasing likelihood of CFS and CI in COVID-19 survivors as the number of acute COVID-19 symptoms increases.